2019
DOI: 10.1098/rspb.2019.1647
|View full text |Cite
|
Sign up to set email alerts
|

Burrowing detritivores regulate nutrient cycling in a desert ecosystem

Abstract: Nutrient cycling in most terrestrial ecosystems is controlled by moisture-dependent decomposer activity. In arid ecosystems, plant litter cycling exceeds rates predicted based on precipitation amounts, suggesting that additional factors are involved. Attempts to reveal these factors have focused on abiotic degradation, soil–litter mixing and alternative moisture sources. Our aim was to explore an additional hypothesis that macro-detritivores control litter cycling in deserts. We quantified the role different o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 46 publications
(70 reference statements)
1
19
0
1
Order By: Relevance
“…For example, Sagi et al (2019) found a 1.5-fold increase in ammonium, a twofold increase in nitrate, and a 1.3-fold increase in phosphate concentrations near the vertical burrow of desert isopods (Hemilepistus reaumuri) compared with 20 cm away from the burrow. Notably, nutrient enrichment was not limited to the burrow walls but extended up to a distance of about 10 cm from the vertical burrows [25]. In another example, Nutting et al (1987) measured an 11-fold increase in ammonium and a twofold increase in phosphate in soil brought to the surface by Sonoran desert termites compared to adjacent surface soil [49].…”
Section: Regulation Of Plant Litter Decomposition Via Engineering Effectsmentioning
confidence: 97%
See 3 more Smart Citations
“…For example, Sagi et al (2019) found a 1.5-fold increase in ammonium, a twofold increase in nitrate, and a 1.3-fold increase in phosphate concentrations near the vertical burrow of desert isopods (Hemilepistus reaumuri) compared with 20 cm away from the burrow. Notably, nutrient enrichment was not limited to the burrow walls but extended up to a distance of about 10 cm from the vertical burrows [25]. In another example, Nutting et al (1987) measured an 11-fold increase in ammonium and a twofold increase in phosphate in soil brought to the surface by Sonoran desert termites compared to adjacent surface soil [49].…”
Section: Regulation Of Plant Litter Decomposition Via Engineering Effectsmentioning
confidence: 97%
“…In the Chihuahuan desert, termites are responsible for 50% of the leaf litter removal [11,22,23], and in the hot and dry Baza basin detritivores increased plant litter mass loss by a factor of 1.23 [24]. In the Negev desert macro-detritivores accounted for 89% of the litter removal, and the highest removal rate was observed in the dry and hot summer when the contribution of microorganisms and mesofauna was negligible [25].…”
Section: Regulation Of Plant Litter Removalmentioning
confidence: 99%
See 2 more Smart Citations
“…soil animals that feed on decomposing litter, assimilate a part of it and typically return the largest part to the soil as faeces ('litter conversion into detritivore faeces' hereafter) 6 . Studies from temperate 7 , Mediterranean 8 , tropical 9 and arid 10 ecosystems reported that large portions of annual litterfall are consumed by detritivores and converted into faeces. This conversion entails physical changes with a reduction of initially intact litter to minute particles that constitute the faeces (referred to as comminution or fragmentation in the literature 2 ) and chemical changes with a partial digestion of the litter passing through detritivore guts 6 .…”
mentioning
confidence: 99%